2021
DOI: 10.1177/17479541211062596
|View full text |Cite
|
Sign up to set email alerts
|

The video feedback viewing in novice weightlifters: Total control strategy improves snatch technique during learning

Abstract: This study aimed at comparing the efficiency of two viewing control strategies, total control versus partial control, in correcting the snatch technique in school-aged boys (10–12 years old). Thirty-nine participants, with 2 months of weightlifting training experience, were divided into three groups: total control, partial control, or a control group. The Kinovea version 0.8.15 software was used to measure the kinematic parameters of the snatch technique before (T0) and after six learning sessions (T1). Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The reduction in this displacement is a crucial predictor of the efficacy of the lift in snatch exercise. In fact, previous studies by Souissi et al 2 declared that this phase is the least complex in the snatch exercise and which takes place at low speed. Regarding the other snatch complex phases, our results have shown a significant improvement in the vertical displacement of the bar at the catch position (VTR: 22.89%) and the difference in the distance from the right and left trajectory of the bar (Diff-Tr: 31.06%) only at T1.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The reduction in this displacement is a crucial predictor of the efficacy of the lift in snatch exercise. In fact, previous studies by Souissi et al 2 declared that this phase is the least complex in the snatch exercise and which takes place at low speed. Regarding the other snatch complex phases, our results have shown a significant improvement in the vertical displacement of the bar at the catch position (VTR: 22.89%) and the difference in the distance from the right and left trajectory of the bar (Diff-Tr: 31.06%) only at T1.…”
Section: Discussionmentioning
confidence: 96%
“…Another possible reason for this improvement can be due to the high number of questions asked by (QS) group learners during the video feedback viewing in blocks 5, 6, 7, and 8. A previous study by Souissi et al 2 showed that the high number of questions asked by participants is a sign of an active engagement in the evaluation of their own snatch performance, which could have led to the development of error detection and correction mechanisms. The imaginal coding of detected errors is an important step in the process of rebuilding a motor program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 , 18 Researchers have also shown that video feedback can empower athletes to watch their performance at their adequate pace, through pausing, rewinding, and slowing down the video-based content to learn at a rate that matches their needs. 19 However, Souissi et al 12 , 20 declared that beginners are not able to detect all the technical errors in their snatch movements displayed in the video feedback. Therefore, for a more fruitful motor learning experience, Souissi et al 12 suggested that the integration of a pedagogical activity (in the form of a comparison of the videotaped performance against key images of the task) during the video feedback viewing helps the learner to further detect and correct technical errors.…”
Section: Introductionmentioning
confidence: 99%